Surgical Treatment of Post-Amputation Foot Deformations in Diabetic Neuropathy - P. S. Bardyugov; M. V. Parshikov; N. V. Yarygin (Неотложная медицинская помощь)
Relevance The number of amputations performed on patients with diabetic foot syndrome is increasing all over the world. Almost half of these operations are the so-called “minor amputations” carried out within the foot. The high recurrence rate of neuropathic ulcers, impaired biomechanics, and a decrease in the quality of life of patients after these surgeries encourage the study of this problem and the search for possible treatment options due to the capabilities of surgical treatment for post-amputation foot deformities.Aim of study To evaluate the nature of surgical interventions for post-amputation foot deformities in patients with diabetic neuropathy.Material and methods The literature search was carried out in the databases of medical publications PubMed, CyberLeninka, Google Scholar, Scopus, Medline, eLIBRARY among articles in English and Russian. The search was performed using the following terms: transmetatarsal resection, diabetic foot syndrome, transmetatarsal amputation, minor amputation.Results Surgical treatment methods for deformities after amputation of part of the forefoot are widely presented in the world literature and are more studied. The possibilities of correcting foot deformities that occurred after amputation of the entire anterior section (from transmetatarsal amputation to the level of the Chopart`s joint) are less covered, this direction and methods have been studied to a lesser extent.Conclusions Surgical methods for the correction of post-amputation foot deformities have firmly entered the wide international practice. Their effectiveness is confirmed by studies with a high level of evidence. Nevertheless, a wider, academic research of the problem of orthopedic status in patients with this pathology and the corresponding methods of surgical treatment is required.